2023
DOI: 10.3390/plants12051189
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth, Yield, and Fruit Size Improvements in ‘Alicia’ Papaya Multiplied by Grafting

Abstract: Papaya (Carica papaya L.) is one of the few fruit crops still propagated by seeds. However, its trioecious condition and the heterozygosity of the seedlings make urgent the development of reliable vegetative propagation procedures. In this experiment, we compared, in a greenhouse sited in Almería (Southeast Spain), the performance of plantlets of ‘Alicia’ papaya originated by seed, grafting, and micropropagation. Our results show that grafted papayas were more productive than seedlings papayas (7% and 4% for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…This corresponds with the hazelnut data, where micropropagated plants showed higher growth rate than grafted and own-rooted plants, reaching, at the end of the trial, in the fourth growing season, similar canopy volumes to both grafted and own-rooted ones. Salinas et al (2023), comparing the performance of plantlets of papaya originated by seed, grafting, and micropropagation, found that in vitro micropropagated papayas were the least productive, even if they bloomed earlier and set fruit at desirable trunk height, because they were less tall and thick. Hernandez et al (1997) found in kiwifruit that commercial production first harvest was significantly higher in grafted plants, even if the following years plants obtained from cuttings showed greater vigor and higher cumulative and commercial yield.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds with the hazelnut data, where micropropagated plants showed higher growth rate than grafted and own-rooted plants, reaching, at the end of the trial, in the fourth growing season, similar canopy volumes to both grafted and own-rooted ones. Salinas et al (2023), comparing the performance of plantlets of papaya originated by seed, grafting, and micropropagation, found that in vitro micropropagated papayas were the least productive, even if they bloomed earlier and set fruit at desirable trunk height, because they were less tall and thick. Hernandez et al (1997) found in kiwifruit that commercial production first harvest was significantly higher in grafted plants, even if the following years plants obtained from cuttings showed greater vigor and higher cumulative and commercial yield.…”
Section: Discussionmentioning
confidence: 99%
“…Papaya ( Carica papaya L.) originates from Central and South America but is cultivated in all tropical regions [ 1 ]. The total world papaya area has reached 468,731 hectares and global production of papaya is estimated to rise by 2.1 percent each year, up to 16.6 million tons in 2029 [ 2 , 3 ]. But papaya is a tropical fruit that is prone to physical damage and disease, which poses challenges for its storage and transportation [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%